2014
DOI: 10.1055/s-0034-1385886
|View full text |Cite
|
Sign up to set email alerts
|

What is the Best Method for Assessing Lower Limb Force-Velocity Relationship?

Abstract: This study determined the concurrent validity and reliability of force, velocity and power measurements provided by accelerometry, linear position transducer and Samozino's methods, during loaded squat jumps. 17 subjects performed squat jumps on 2 separate occasions in 7 loading conditions (0-60% of the maximal concentric load). Force, velocity and power patterns were averaged over the push-off phase using accelerometry, linear position transducer and a method based on key positions measurements during squat j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
79
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 38 publications
20
79
1
3
Order By: Relevance
“…Such results have been consistently observed from cycling [1316], jumping [1719], running [20, 21], leg push offs [4, 2224], lifting [13, 25, 26] etc. Of utmost importance is that most of the cited studies revealed the correlation coefficients of the linear model applied to individual sets of data well above 0.9.…”
Section: Force-velocity Relationship Of Muscles Performing Functiosupporting
confidence: 55%
See 1 more Smart Citation
“…Such results have been consistently observed from cycling [1316], jumping [1719], running [20, 21], leg push offs [4, 2224], lifting [13, 25, 26] etc. Of utmost importance is that most of the cited studies revealed the correlation coefficients of the linear model applied to individual sets of data well above 0.9.…”
Section: Force-velocity Relationship Of Muscles Performing Functiosupporting
confidence: 55%
“…In addition, no significant differences in the strength of the relationships were found between the linear and polynomial regression models applied on the same sets of F and V data [18, 19, 25] suggesting that the assessed F-V relationships could be considered linear for further computation. Of importance could also be that the parameters depicting the maximum F, V and P of the tested muscles (i.e., the regression parameters F 0 , V 0 , and P 0 , respectively) proved to be highly reliable [17, 18, 2426] and at least moderately valid [15, 1719]. Finally, several studies have already showed that the same parameters could also be sensitive enough to detect the differences among various populations regarding the discussed muscle capacities [13, 16, 23, 27].…”
Section: Force-velocity Relationship Of Muscles Performing Functiomentioning
confidence: 99%
“…The relative difference between actual and optimal F-v profiles for a given individual represents the magnitude and the direction of the unfavorable balance between force and velocity qualities (i.e., force-velocity imbalance, FV imb in %), which makes possible the individual determination of force or velocity deficit. The actual individual F-v profile and P max can be easily determined from a series of loaded vertical jumps (Samozino et al, 2008, 2014; Jiménez-Reyes et al, 2014, 2016; Giroux et al, 2015, 2016), while the optimal F-v profile can be computed using previously proposed equations based on a biomechanical model (Samozino et al, 2012, 2014). For a given P max , vertical jump performance has been shown to be negatively correlated to FV imb , which supports the importance of considering this individual characteristic in addition to P max when designing training programs to improve ballistic performance (Samozino et al, 2012, 2014; Morin and Samozino, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This method, based on macroscopic modelling of body mass displacement and the associated mechanical external work, requires only body mass, hPO and jump height. The initial reliability and concurrent validity was tested against reference force plate measurements [8], and was confirmed in subsequent studies from other authors, including additional load conditions and application to CMJ [7,46,47]. In this method, the mean power produced during a jump was computed as:…”
Section: 3mentioning
confidence: 84%